Stress-induced electronic structure modulation of manganese-incorporated Ni2P leading to enhanced activity for water splitting - Sarkar, Shreya; Dheer, Lakshay; Vinod, C. P.; Thapa, Ranjit; Waghmare, V. Umesh; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
The cornerstone of the emerging hydrogen economy is hydrogen production by water electrolysis with concomitant oxygen generation. Incorporating a third element in metal phosphides can tune the crystalline and electronic structure, hence improving the electrocatalytic properties. In this work, Mn-doped Ni2P with varying ratios of Mn and Ni has been explored as excellent catalysts for water splitting. A complete cell made of the best catalyst Ni1.5Mn0.5P electrodes showed low voltage of 1.75 V at a current density of 10 mA cm(-2) due to enhanced electrical conductivity, induction of tensile stress, enhanced electrochemical surface area, and increased electric dipole upon Mn incorporation.
Keywords: Electronic Structure; hydrogen evolution reaction; Oxygen Evolution Reaction; phosphides; water splitting

Conductive interface promoted bifunctional oxygen reduction/evolution activity in an ultra-low precious metal based hybrid catalyst (vol 57, pg 1951, 2021) - Sarkar, Shreya; Varghese, Merin; Vinod, C. P.; Peter, Sebastian C. (Chemical Communications, 2021)

Conductive interface promoted bifunctional oxygen reduction/evolution activity in an ultra-low precious metal based hybrid catalyst - Sarkar, Shreya; Varghese, Merin; Vinod, C. P.; Peter, Sebastian C. (Chemical Communications, 2021)
Ultra low PtPd alloy deposited on Ni12P5 nanostructures (PtPd/Ni12P5) exhibited enhanced ORR activity (onset: 1.003 V and E-1/2:0.95 V) on par with commercial Pt/C and superior OER activity with 81% reduction of the precious metal compared to the commercial catalyst.

Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.

Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides

Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme

Potential- and time-dependent dynamic nature of an oxide-derived pdin nanocatalyst during electrochemical CO2 reduction - Bagchi, Debabrata; Sarkar, Shreya; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2022)
Electrochemical reduction of CO2 into valuable fuels and chemicals is a promising route of replacing fossil fuels by reducing CO2 emissions and minimizing its adverse effects on the climate. Tremendous efforts have been carried out for designing efficient catalyst materials to selectively produce the desired product in high yield from CO2 by the electrochemical process. In this work, a strategy is reported to enhance the electrochemical CO2 reduction reaction (ECO2RR) by constructing an interface between a metal-based alloy (PdIn) nanoparticle and an oxide (In2O3), which was synthesized by a facile solution method. The oxide-derived PdIn surface has shown excellent eCO(2)RR activity and enhanced CO selectivity with a Faradaic efficiency (FE) of 92.13% at -0.9 V (vs RHE). On the other hand, surface PdO formation due to charge transfer on the bare PdIn alloy reduces the CO2RR activity. With the support of in situ (EXAFS and IR) and ex situ (XPS, Raman) spectroscopic techniques, the optimum presence of the Pd-In-O interface has been identified as a crucial parameter for enhancing eCO(2)RR toward CO in a reducing atmosphere. The influence of eCO(2)RR duration is reported to affect the overall performance by switching the product selectivity from H-2 (from water reduction) to CO (from eCO(2)RR) on the oxide-derived alloy surface. This work also succeeded in the multifold enhancement of the current density by employing the gas diffusion electrode (GDE) and optimizing its process parameters in a flow cell configuration.
Keywords: CO2 reduction; Electrochemistry; heterostructure interface; in situ mechanism; nanocatalyst